The Existance of Bapokat Tradition at Batahan District in Mandailing Natal Regency - Muhammad Afdhaluz Zikri Lubis; Robert Sibarani (Tradition and Modernity of Humanity, 2024)
Bapokat is a tradition that is still carried out today by the Minangkabau ethnic in Batahan. However, Bapokat in Batahan has several differences from that of the Minangkabau ethnic in West Sumatra, so of course the values contained in it are different. This research aims to determine the Bapokat tradition carried out by the Minangkabau ethnic who live in Batahan. This research uses an anthropolinguistic approach with qualitative methods. The data obtained is in the form of answers to the researcher's questions. From this research it can be concluded that the Bapokat tradition still exists in the Minangkabau ethnic in Batahan.